2007
DOI: 10.1021/cg060494x
|View full text |Cite
|
Sign up to set email alerts
|

Templating the Nucleation of Calcium Oxalate Monohydrate via Micropatterned Self-Assembled Monolayers on Gold

Abstract: Controlling both the nucleation and the growth of crystalline materials requires the confinement of a space wherein nucleation is induced and necessitates transport of ions to the newly formed nucleus. Micropatterned self-assembled monolayers (µP SAMs) of alkanethiolates on gold have been used at length to mimic natural organic templates as they are a facile way to create spatially constrained microenvironments for nucleation and consequently control ion flow to active nucleation sites. Here, we present µP SAM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…30 However, these experiments have been mostly carried out on crystals grown on a template surface directly. 22,[25][26][27] To the authors' knowledge, there have been no studies, so far, which have shown the influence of surface templates on crystallization within the bulk solution and within a representative reaction vessel size.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 However, these experiments have been mostly carried out on crystals grown on a template surface directly. 22,[25][26][27] To the authors' knowledge, there have been no studies, so far, which have shown the influence of surface templates on crystallization within the bulk solution and within a representative reaction vessel size.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, there have been rather few papers regarding the crystallization of organic crystals by surfaces templating. However, inorganic crystals especially CaCO 3 , crystallized on templated surfaces have been found to result in different polymorphs having a variety of interesting crystal shapes.…”
Section: Introductionmentioning
confidence: 99%